Corporate governance and records management in private and public hospitals in Ghana. (20th March 2017) - Appiah, Kingsley Opoku; Amos, Kon-Naah Moomin; Bashiru, Jebuni; Drammeh, Palamin Habib; Tuffour, Sharita
Abstract : Purpose: This paper aims to explore the link between corporate governance and records management in hospitals in Ghana. Design/methodology/approach: Questionnaires are used to collect data from 500 management staff from 85 hospitals (public and private). The respondents comprise 134, 211, 100 and 55 from the Eastern, Ashanti, Northern and Upper West Regions in Ghana, respectively. Three-stage least-squares and ordinary least square regressions are used to establish the relationship between corporate governance and records management. Findings: Corporate governance exhibits a positive and significant relationship with security and records management. Records management, in turn, displays a positive and significant relationship with security, transparency, corporate governance and region, but not accountability. Research limitations/implications: The study is based on 85 hospitals consisting of 20 private and 65 public hospitals across four regions out of ten in Ghana, implying that the findings may not be applicable in the six regions omitted. Practical implications: The findings may assist hospital management within the sub-Sahara Africa to design training programs on records management and/or corporate governance. Originality/value: This study adds to the body of knowledge about records management and corporate governance from the sub-Sahara perspective. Specifically, the authors widen the scope on corporate governance and records management by emphasising on management, a marked departure from other studies conducted on Ghana.